The Social Family Factors and Its Influence upon The Son's Academic Excellence A field research for students of the Elites' School in Lattakia - Saleh, Nabil (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The goal beyond this research is to highlight the influence of the social family factors on the academic excellence of sons. This research sample was on (240) of (408) male and female students who are in the first, second and the third secondary stages for the school year 2016-2017. For reaching the intended goals of this research, a questionnaire was adopted as a tool for collecting both the preliminary data and the data related to the variables of this research. The results of the research assured that the number of the family members does not have that clear effect on the academic excellence and most of the students do not get negatively affected by the parental divorce or even by the absence of one of the parents so this factor does not affect the sons' academic excellence. Also, the birth order in any student's family does not affect positively or negatively the student's academic excellence. The good and healthy relationship between the father and the sons has a clear effect on their academic excellence but, on the other hand, the relationship between the mother and the sons does not have that clear effect on their academic excellence. Moreover, this research stated that there is a positive link between the parents' moderate control and treatment practiced inside the family towards the sons and the sons' academic excellence. On the other side, this research stated that there is no link between the parents' dominating control and treatment towards the sons and the sons' academic excellence.